1999
DOI: 10.1016/s0140-3664(99)00055-9
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic reward net model for performance analysis of prioritized DQDB MAN

Abstract: The performance of prioritized DQDB MAN under bursty tra c environment is studied in this paper. The tagged node model is adopted to simplify the analysis. The processes of the packet arrivals to the tagged node, the empty-slot pattern from upstream, and the request pattern from downstream are assumed to be Markov M o dulated Poisson Processes, a more general and appropriate model to capture the bursty characteristics existing in the tra c ows in high-speed networks. A s t o c hastic reward nets model for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A SRN is a modeling technique that is concise in its specification and closer to a designer's intuition about what a model should look like. SRNs have been extensively used for performance, reliability and performability analysis of a variety of systems [15,6,7,18,8,11]. The work closest to the proposed research is reported by Ramani et al [15], where SRNs are used for the performance analysis of the CORBA event service.…”
Section: Srn Modelmentioning
confidence: 99%
“…A SRN is a modeling technique that is concise in its specification and closer to a designer's intuition about what a model should look like. SRNs have been extensively used for performance, reliability and performability analysis of a variety of systems [15,6,7,18,8,11]. The work closest to the proposed research is reported by Ramani et al [15], where SRNs are used for the performance analysis of the CORBA event service.…”
Section: Srn Modelmentioning
confidence: 99%
“…A SRN is a modeling technique that is concise in its specification and closer to a designer's intuition about what a model should look like. SRNs have been extensively used for performance, reliability and performability analysis of a variety of systems [10], [11], [12], [13], [14], [15]. The work closest to the proposed research is reported by Ramani et al [10], where SRNs are used for the performance analysis of the CORBA event service.…”
Section: Srn Modelmentioning
confidence: 99%